Current advances in T-cell-based cancer immunotherapy. (December 2014) - Wang, Mingjun; Yin, Bingnan; Wang, Helen Y; Wang, Rong-Fu
Cancer is a leading cause of death worldwide; due to the lack of ideal cancer biomarkers for early detection or diagnosis, most patients present with late-stage disease at the time of diagnosis, thus limiting the potential for successful treatment. Traditional cancer treatments, including surgery, chemotherapy and radiation therapy, have demonstrated very limited efficacy for patients with late-stage disease. Therefore, innovative and effective cancer treatments are urgently needed for cancer patients with late-stage and refractory disease. Cancer immunotherapy, particularly adoptive cell transfer, has shown great promise in the treatment of patients with late-stage disease, including those who are refractory to standard therapies. In this review, we will highlight recent advances and discuss future directions in adoptive cell transfer based cancer immunotherapy.